2006
DOI: 10.1093/brain/awl258
|View full text |Cite
|
Sign up to set email alerts
|

Facial onset sensory and motor neuronopathy (FOSMN syndrome): a novel syndrome in neurology

Abstract: A 'syringomyelia-like' syndrome has been infrequently reported in neurological disorders such as Tangiers disease and lepromatous leprosy. This study reports a novel 'syringomyelia-like' syndrome in four adult male patients, which we have termed facial onset sensory and motor neuronopathy, or FOSMN syndrome, that appears to have a neurodegenerative aetiology. Clinical, neurophysiological and pathological data of four patients were reviewed, including the autopsy in one patient. Four male patients (mean age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 32 publications
11
119
2
Order By: Relevance
“…A neurodegenerative process was proposed because of the absence of inflammatory cell infiltrates in the nervous tissues and the lack of response to various immunotherapies [1]. In the present case, however, the responses to immunotherapies supported a contribution from an immunological mechanism resembling CIDP [11].…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…A neurodegenerative process was proposed because of the absence of inflammatory cell infiltrates in the nervous tissues and the lack of response to various immunotherapies [1]. In the present case, however, the responses to immunotherapies supported a contribution from an immunological mechanism resembling CIDP [11].…”
Section: Discussionmentioning
confidence: 47%
“…In 2006, Vucic et al [1] reported a novel syndrome named FOSMN syndrome in four Caucasian men in their 40s. They suggested neuronopathy, because of reduced SNAP and CMAP amplitudes together with the widespread occurrence of denervation potentials in bulbar and limb muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial onset sensory and motor neuronopathy (FOSMN) was first described by Vucic et al in 2006;1 there have been 30 cases reported to date 1 2. Its cardinal features are onset with asymmetrical facial numbness or paraesthesia, with impaired light touch and pain sensation evolving in a mantle distribution, followed by bulbar symptoms with facial atrophy and weakness.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although a previous study assessed infraorbital nerve pathology in one patient, 2 no studies have directly aimed at investigating trigeminal nerve fiber damage in patients with FOSMN and assessing the involvement of the different sensory nerve fiber populations in this disease. Having this information might help understand the pathophysiology of FOSMN and thus guide its clinical management.…”
Section: Differential Trigeminal Myelinated and Unmyelinated Nerve Fimentioning
confidence: 99%